Hydrogen storage properties of a destabilized MgH2-Sn system with TiF3 addition - Ismail, M. (Elsevier Ltd, 2016)
The MgH2-Sn system is considered a promising reactive metal composite for hydrogen storage. Several ratios of MgH2-Sn (2:1, 3:1 and 4:1) destabilized system were investigated experimentally using a ball milling method. Based on the temperature-programme desorption results, the onset dehydrogenation temperature of the MgH2-Sn composite was consisted of two steps in the range of 235-250 °C and 325-340 °C. TiF3 catalyst was introduced to enhance the desorption temperature of the MgH2-Sn (4:1) system. The onset dehydrogenation temperature of the 4MgH2-Sn-10 wt% TiF3 composite was reduced to approximately 100 °C and 205 °C compared to the MgH2-Sn (4:1) and the as-milled MgH2. The Kissinger analysis established that the apparent activation energy for the first stage of the 4MgH2-Sn composite was reduced from 149.0 kJ/mol to 114.0 kJ/mol after adding 10 wt% TiF3. However, the addition of TiF3 did not result in improvement of the absorption process. The improvement of the dehydrogenation properties of the MgH2-Sn composite with the addition of TiF3 was due to the formation of Ti-containing and F-containing species. These species played a catalytic role in improving the dehydrogenation properties of the MgH2-Sn system.